Sposobnost besednega učenja bolnikov v subakutnem obdobju po možganski kapi v odnosu s hitrostjo in kapaciteto procesiranja podatkov - Starovasnik Žagavec, Barbara (Rehabilitacija (Ljubljana), 2020)
Background: The capacity to learn new information after stroke is important for a number of reasons, especially for a favorable cognitive and motor outcome. The base for an efficient encoding process are normal information speed processing and attention capacity, which are compromised during the first year after first stroke. The aim of our study was to explore the relationship between different memory deficits after stroke in correlation with information processing speed and attention capacity. Methods: The 6-month study included 27 patients after stroke admitted to the Stroke Rehabilitation Unit during the first year after stroke. Neuropsychological data were collected using the Alertness subtest (TAP-M) and various memory and attention subtest from the screening battery (RBANS test). Results: Processing speed was impaired in the majority of patients involved (52 % on the simple reaction time task, 40 % on the coding task). Attention capacity was independently associated with immediate recall. Time of stroke onset was also relevant for immediate recall efficiency. The delayed story recall differed with respect to brain lesion location and type of stroke. Conclusions: Our pilot study showed correlations between attention capacity and verbal memory, but in slightly different patterns depending on the requirements of individual tasks and patient characteristics (location and type of stroke).
Keywords: hitrost procesiranja; information processing speed; Learning; možganska kap; prepoznava; priklic; psychology; recall; recognition; rehabilitation; Stroke; učenje